(untitled) (Scientific journal of the Fergana State University, 2024)
The article reveals the concept of civil society, which is the most effective solution to managing society invented by humanity, and its characteristics. The opinions of intellectual scientists on this matter are analyzed. It is also indicated that improving the legal culture of the population is the basis for the development of civil society institutions, and reforms in this direction are also indicated.